Step-by-step explanation:
6x - 3x^2 + 2x^2 -2x = 5x^2 + 15x
4x -x^2 = 5x^2 + 15x
-11x - 6x^2 = 0
-6x^2 - 11x = 0
use the quadratic formula
(-b±√(b²-4ac))/(2a)
If we consider x having any other value then 0,1 or 2 then the answer is b.2x(x-1)
Step-by-step explanation:
<em>1</em><em>1</em><em>/</em><em>2</em><em>,</em><em> </em>-11, 22, <em>-</em><em>4</em><em>4</em><em>,</em><em> </em>88, -176
common ratio : 22/(-11) = -2
It means the speed (velocity) was constant - the object traveled the same distance per time period throughout the graph.